Applicability of technological development in oral rehabilitation: case report (Research, Society and Development, 2021)
Rehabilitation dentistry is undergoing a major evolution in all areas of knowledge, whether through scientific research, development of surgical techniques and development of materials. With the emergence of new technologies, more resources are being added to the daily clinic, since materials and techniques help from diagnosis to the manufacture of prostheses on implants. The objective of this clinical case report is to demonstrate the importance of associating several areas of knowledge in implant-supported rehabilitation, valuing the benefits of using cone beam computed tomography, the CAD / CAM system, intraoral scanners and adhesive techniques in rehabilitation. A 54-year-old patient sought treatment at Fundecto-USP (Fundação Faculdade de Odontologia associated with FOUSP) with a complaint of dental absence in the region of elements 14 and 15, in addition to complaints regarding aesthetics in the anterior region. The diagnosis was made through assembly in a semi-adjustable articulator, photographs and diagnostic waxing. Despite the absence of two elements, rehabilitation with implantation of only element 15 and an increase in elements 16 and 13 was planned. Cone beam computed tomography allowed to identify the absence of sufficient bone height for implant installation in the region of 15, so it was planned installation of the implant with simultaneous lifting of the maxillary sinus membrane. Through intraoral scanning, CAD / CAM technology and clinical information, the virtual waxing project for future crowns was carried out. After approval, the models were printed, reamed the wax crowns, tasted the wax crowns and ceramic reamed crowns. Based on the experience, it seems reasonable to conclude that technological developments have made complex dental rehabilitation faster, more effective and predictable.